Two Hopeless Causes: Education and Incarceration - Notar, Charles E. (Advances in Social Sciences Research Journal, 2019)
There are a myriad study providing cost figures for education and prisons in the United States. Most have in the American prison system an estimated 2.2 million inmates and with an estimated cost of 80 billion that eclipses the GDP of 133 nations. That’s on average 36,000 per prisoners per year. Current expenditures for public elementary and secondary schools are projected to be 623.5 billion for the 2017–18 school year. The current expenditure per student is projected to be 12,300 for the 2017–18 school year. The article purports that the financing policies of education and incarceration are not providing the results intended.